PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, DAN OPINI AUDITOR TERHADAP AUDIT DELAY - Herwinda Astuti (2017)
The purpose of this study was to examine the effect of profitability, Company Size, Leverage and Audit Opinion to Auditor Delay (research study was conducted on Mining Companies Listed in Indonesia Stock Exchange since 2012 to 2015 period). The population in this study some 44 mining companies listed on the Indonesia Stock Exchange since 2012 until 2015. The sample period are mining company in accordance with criteria set that is purposive sampling. Statistical method used is multiple linear regression, normality test is done to determine the value of Min, Max, Mean and classical assumption beforehand that includes normality test, multikoloniaritas, auto correlation test, test and test hypotheses Heteroskidastity using t-statistics and F- statistics. The results of this study indicate that (1) Variable profitability, Company Size, Leverage and Auditor Opinion partially significant influence on Audit Delay. (2) profitability, Company Size, Leverage and Auditor Opinion Mining Company simultaneously significantly influence the Audit Delay.